Aktivitas Radical Scavenging Melalui Penghambatan Nitric Oxide Madu Hutan Asal Kolaka Timur Pada Sel Makrofag Raw 264.7 - Hariana; Wahyuni; Lidya Agriningsih Haruna; La Ode Muh. Julian Purnama; Adryan Fristiohady (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Forest honey is a natural product rich in bioactive compounds, particularly phenolics and flavonoids, which contribute to its antioxidant and anti-inflammatory properties. East Kolaka, Southeast Sulawesi, is recognized as a potential source of forest honey; however, scientific data regarding its biological activity remain limited. This study aimed to evaluate the antioxidant and anti-inflammatory activities of forest honey from East Kolaka using in vitro and in vivo approaches. Antioxidant activity was assessed using DPPH, ABTS, and β-carotene bleaching assays, while anti-inflammatory activity was evaluated through inhibition of nitric oxide production in LPS-induced RAW 264.7 macrophage cells and a xylene-induced mouse ear edema model. The results demonstrated notable antioxidant activity, with IC₅₀ values of 68.16 ± 1.18 mg/L (DPPH), 56.36 ± 3.72 mg/L (ABTS), and 4.11 ± 0.66 mg/L (BCB). Additionally, the honey significantly suppressed nitric oxide production in vitro and reduced ear edema in vivo, with the highest dose showing comparable effectiveness to sodium diclofenac. These findings indicate that East Kolaka forest honey has promising potential for development as a functional food or nutraceutical derived from local natural resources.